Case Report: Expanded delineation of phenotype of TRPM3-related neurodevelopmental disorders - Pawelak, Agnieszka; Polczyk, Artur; Wolańska, Ewelina; Kłaniewska, Magdalena; Biela, Mateusz; Basiak, Aleksander; Franaszczyk, Maria; Rydzanicz, Małgorzata; Płoski, Rafał; Śmigiel, Robert (Frontiers in Pediatrics, 2024)
The TRPM3 gene, part of the transient receptor potential (TRP) cation channel family, plays crucial roles in sensory perception and ion transport. Mutations in TRPM3 are linked to a range of neurological and developmental disorders. The c.2509G>A variant specifically leads to a substitution at position 837 in the protein, which is likely critical for its normal function. This study presents a male pediatric patient with a pathogenic TRPM3 variant c.2509G>A (p.( Val837Met)), contributing to a complex clinical phenotype characterized by developmental delays, significant hypotonia, and neurological abnormalities. The patient demonstrated delayed motor milestones, including the inability to sit independently until 20 months, and abnormal EEG findings without epileptic seizures. Ophthalmologic issues, such as hyperopia and astigmatism, were also identified. Behavioral abnormalities and cognitive impairment aligned with previous reports of TRPM3-related neurodevelopmental disorders. This case highlights the phenotypic variability linked to the p.(Val837Met) variant and emphasizes the need for further research into effective therapeutic strategies for TRPM3-associated conditions.